Signaling networks in TMPRSS2-ERG positive prostate cancers: Do we need a Pied Piper or sharpshooter to deal with "at large” fused oncoprotein - Lin, X.; Qureshi, M. Z.; Romero, M. A.; Yaylim, I.; Arif, S.; Ucak, I.; Fayyaz, S.; Farooqi, A. A.; Mansoor, Q.; Ismail, M. (Cellular and Molecular Biology, 2017)
Overwhelmingly increasing scientific evidence has provided near complete resolution of prostate cancer landscape and it is now more understandable that wide ranging factors underlies its development and progression. Increasingly it is being realized that genetic/epigenetic factors, Intra-tumoral and inter-tumoral heterogeneity, loss of apoptosis, dysregulations of spatio-temporally controlled signaling cascades, Darwinian evolution in response to therapeutic pressures play instrumental role in prostate carcinogenesis. Moreover, multi-directional patterns of spread between primary tumors and metastatic sites have also been studied extensively in prostate cancer. Research over the years has gradually and systematically revealed closer association between tumor phenotype and type of gene fusion. Latest developments in deep sequencing technologies have shown that gene fusions originate in a non-random, cell type dependent manner and are much more frequent than previously surmised. These findings enabled sub-classification and categorization of seemingly identical diseases. Furthermore, research methodologies have shown that many gene fusions inform us about risk stratification and many chimeric proteins encoded by the fused genes are being studied as drug target/s. We partition this multi-component review into the molecular basis of formation of fusion transcripts, how protein network is regulated in fusion positive prostate cancer cells and therapeutic strategies which are currently being investigated to efficiently target fusion transcript and its protein product.